Bones of Complexity : Bioarchaeological Case Studies of Social Organization and Skeletal Biology - Larsen, Clark Spencer; Cohen, Mark Nathan; Harvey, Amanda R.; Klaus, Haagen D. (Book collections on Project MUSE., 2017)
This volume examines the various interrelationships between social structures, skeletal biology, and health outcomes in antiquity. Bringing together studies by physical anthropologists, archaeologists, and economists, the volume attempts to gain a better understanding of the potential effects of social complexity on human biology from ancient Egypt to South America.